Speech in a consecutive series of children born with cleft lip and palate with and without syndromes and/or additional malformations - Kristina Klintö; Maria Sporre; Magnus Becker (BMC, 2021)
Abstract Background When evaluating speech in children with cleft palate with or without cleft lip (CP/L), children with known syndromes and/or additional malformations (CP/L+) are usually excluded. The aim of this study was to present speech outcome of a consecutive series of 5-year-olds born with CP/L, and to compare speech results of children with CP/L + and children with CP/L without known syndromes and/or additional malformations (CP/L-). Methods One hundred 5-year-olds (20 with CP/L+; 80 with CP/L-) participated. All children were treated with primary palatal surgery in one stage with the same procedure for muscle reconstruction. Three independent judges performed phonetic transcriptions and rated perceived velopharyngeal competence from audio recordings. Based on phonetic transcriptions, percent consonants correct (PCC) and percent non-oral errors were investigated. Group comparisons were performed. Results In the total group, mean PCC was 88.2 and mean percent non-oral errors 1.5. The group with bilateral cleft lip and palate (BCLP) had poorer results on both measures compared to groups with other cleft types. The average results of PCC and percent non-oral errors in the CP/L + group indicated somewhat poorer speech, but no significant differences were observed. In the CP/L + group, 25 % were judged as having incompetent velopharyngeal competence, compared to 15 % in the CP/L- group. Conclusions The results indicated relatively good speech compared to speech of children with CP/L in previous studies. Speech was poorer in many children with more extensive clefts. No significant differences in speech outcomes were observed between CP/L + and CP/L- groups.